Evaluation of physiological and behavioral measures in relation to dental anxiety during sequential dental visits in children - Rayen R; Muthu M; Rao Chandrasekhar; Sivakumar N (Wolters Kluwer Medknow Publications, 2006)
Anxiety is a special variety of fear, experienced in anticipation of threatening stimuli. While some research workers have said that the response of a child improves with the number of visits, many have felt otherwise. The present study is yet another effort to find the patterns of anxiety in children during sequential dental visits. The main aim was to determine the physiological and behavioral variations during sequential dental visits and its impact on age and sex. The study was conducted at the outpatient Department of Pedodontics and preventive dentistry, Meenakshi Ammal Dental College and Hospital, Chennai to evaluate the physiological and behavioural measures of stress and anxiety in children. One hundred and fifteen children, between four and eleven years of age who reported for dental treatment were selected for the study.